The effects of age on antibody response towards COVID-19 vaccination: A Systematic Review - Hendra Ikhwan Gautama; Gatot Soegiarto; Laksmi Wulandari (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2023)
Background: Mortality rate of COVID-19 infection isexceptionally high in the older population. Various vaccines are being rapidly developed as an attempt to halt the pandemic. Although vaccination has been effective in reducing mortality and hospitalization rate in recent months, lower vaccine effectiveness has been reported among older adults.Aim: This review aims to evaluate and summarize current evidence on the effect of age on antibody response towards COVID-19 vaccines. Methods: Literature search was conducted on PubMed, Scopus, ScienceDirect and ProQuest for studies published up to 9th October 2022. The selected studies were assessed The Joanna Briggs critical appraisal tools. Qualitative analysis was then performed for the final studies.Result: A final of 9 studies were included in this review. A majority of the studies evaluated the responses of BNT162b2 or mRNA-1273 vaccine, while 1 study investigated the response towards ChAdOx1 vaccine. Outcomes were measured in term of IgG antibody levels or serum neutralization. Most studies demonstrated significantly lower antibody response and neutralization in older adults compared to younger vaccinees after administration of first and second vaccine dose. However, two studies reported no significant difference in vaccine responses across age groups after third dose administration.Conclusion: This systematic review highlights lowerimmunogenicity towards COVID-19 vaccines in older population. Further research into strategies to improve vaccine responses in the elderly is required to provide sufficient protection for this vulnerable group. Keywords: COVID-19 vaccine, antibody, neutralization, age, elderly